Does rearing an aphid parasitoid on one host affect its ability to parasitize another species?. (30th July 2013) - Vafaie, Erfan K.; Fitzpatrick, Sheila M.; Cory, Jenny S.
Abstract Generalist parasitoids are commonly used for the biological control of insect pests; however, they are often reared on a single host species because this is more practical for commercial production. Few studies have investigated the consequences of rearing a generalist parasitoid on a single host species in terms of performance on other target pests. We investigated the impact of rearing the generalist parasitoid Praon unicum Smith (Hymenoptera: Braconidae, Aphidiinae) on an alternative aphid host Myzus persicae Sulzer (Hemiptera: Aphididae) with respect to its ability to perform on Ericaphis fimbriata Richards (Hemiptera: Aphididae), a pest of highbush blueberries. Parasitoids reared on the two aphid hosts did not differ in physical size measurements. Praon unicum reared on M. persicae had a lower oviposition success over 6 days compared with insects reared on E. fimbriata, mainly as a result of differences early in life. There was no difference in parasitoid egg size, lifetime fertility, age‐specific fertility, female offspring ratio, development time or calculated intrinsic rate of increase from the two aphid hosts. We conclude that there were no negative consequences of rearing P. unicum on M. persicae on its ability to parasitize E. fimbriata, although further field studies would need to be performed to investigate whether natal host influences parasitoid preference.